Omission of nursing care and contributing factors in a hospital of Tabasco, Mexico - López Cocotle, José Juan; Silva Ramos, María Fernanda; Moreno Monsiváis, María Guadalupe; González Angulo, Pedro; Interial Guzmán , Ma Guadalupe (Horizonte Sanitario, 2021)
Objective: to determine the relationship between the omission of nursing care and the contributing factors of a hospital in Tabasco, Mexico. Materials and methods: quantitative, descriptive and correlational study in 50 nurses of different shifts of a public hospital, we used the MISSCARE survey that allows identifying the lost nursing care and the related factors, for the analysis we used descriptive statistics and Spearman's correlation coefficient, we considered what is stipulated in the Regulation of the General Law of Health in Matters of Health Research. Results: the dimension where the greatest omission of care occurred was that of basic care interventions (M= 22.6, SD= 14.2). The factors that contributed most to the omission of nursing care were human resources (M= 75.8, SD= 18.3). Material resources showed weak negative and significant association with continuous assessment interventions (rs= -.318, p= .025). Conclusions: the greatest presence of omission of care falls on basic care interventions, human resource factors are ranked first so that the omission or delay of nursing care interventions occurs; however, only the factors of the material resource referral negatively related to the continuous assessment interventions.